2019
DOI: 10.1017/ice.2019.73
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Attributable Disease Burden and Effects of Interhospital Patient Sharing on Clostridium difficile Infections

Abstract: Objective: To estimate the burden of Clostridium difficile infections (CDIs) due to interfacility patient sharing at regional and hospital levels.Design: Retrospective observational study.Methods: We used data from the Healthcare Cost and Utilization Project California State Inpatient Database (2005)(2006)(2007)(2008)(2009)(2010)(2011) to identify 26,878,498 admissions and 532,925 patient transfers. We constructed a weighted, directed network among the hospitals by defining an edge between 2 hospitals to be th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Following the work of Sewell et al, we fit a static NAM using as a response variable the monthly average number of CDI cases and as covariates the monthly average number of admissions, the median length of stay, the median number of diagnoses, and the proportion of patients over 65. The adjacency matrix A was constructed such that A i j was the monthly average number of transfers from j to i divided by the monthly average number of admissions in hospital j (the diagonal elements A ii were fixed at zero); we row‐normalized the adjacency matrix when fitting the NAM.…”
Section: Patient‐sharing Networkmentioning
confidence: 99%
“…Following the work of Sewell et al, we fit a static NAM using as a response variable the monthly average number of CDI cases and as covariates the monthly average number of admissions, the median length of stay, the median number of diagnoses, and the proportion of patients over 65. The adjacency matrix A was constructed such that A i j was the monthly average number of transfers from j to i divided by the monthly average number of admissions in hospital j (the diagonal elements A ii were fixed at zero); we row‐normalized the adjacency matrix when fitting the NAM.…”
Section: Patient‐sharing Networkmentioning
confidence: 99%
“…In fact, the proportion of shared patients between hospitals was correlated with genetic similarity of MRSA strains from those hospitals [4]. Clostridium difficile infections are likewise shown to be associated with a hospital's network connectivity based on transferred patients [5,6]. There is also differential quality of care effects of inter-hospital critical care transfers, with transferred patients more like to go to higher-quality centers [7,8] and huband-spoke networks for stroke and myocardial infarction with reliance on multiple sites of care [9,10].…”
Section: Introductionmentioning
confidence: 98%
“…Several empirical studies have shown that inter-facility patient movement plays an important role in the dissemination of antimicrobial resistant organisms and CDI throughout healthcare systems, including acute care facilities. [6][7][8] Inter-facility patient sharing, 9,10 including both "direct" same-day patient transfers and "indirect" inter-facility patient movement with intervening non-hospital stays, may contribute to transmission between hospitals. The regional structures of most healthcare systems means that the majority of patient sharing occurs within healthcare regions 11 and genetic similarities of antibiotic resistant organisms reflect regional transfer patterns.…”
Section: Introductionmentioning
confidence: 99%